2021
DOI: 10.1103/physrevlett.127.170405
|View full text |Cite
|
Sign up to set email alerts
|

Network Quantum Steering

Abstract: The development of large-scale quantum networks promises to bring a multitude of technological applications as well as shed light on foundational topics, such as quantum nonlocality. It is particularly interesting to consider scenarios where sources within the network are statistically independent, which leads to so-called network nonlocality, even when parties perform fixed measurements. Here we promote certain parties to be trusted and introduce the notion of network steering and network local hidden state (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…This intrigues a natural problem to explore new way for general multipartite entanglements. While the entanglement is the weakest nonlocality of quantum states, one may explore new hierarchies in terms of the so-called multipartite steering [32,33] or Bell nonlocality [4,24]. This is of special importance for recovering novel multipartite nonlocality beyond bipartite scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…This intrigues a natural problem to explore new way for general multipartite entanglements. While the entanglement is the weakest nonlocality of quantum states, one may explore new hierarchies in terms of the so-called multipartite steering [32,33] or Bell nonlocality [4,24]. This is of special importance for recovering novel multipartite nonlocality beyond bipartite scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the Greenberger-Horne-Zeilinger and W-type assemblages generated by the corresponding multiparty-entangled types can be distilled by local filter [57]. Can our approach be generalized in recent proposed steering networks [58] or multipartite steering [59]? All these questions will be the object of future research.…”
Section: Discussionmentioning
confidence: 98%
“…This intrigues a natural problem to explore new way for general multipartite entanglements. While the entanglement is the weakest nonlocality of quantum states, one may explore new hierarchies in terms of the so-called multipartite steering [40,41] or Bell nonlocality. [4,12] This is of special importance for recovering novel multipartite nonlocality beyond bipartite scenarios.…”
Section: Discussionmentioning
confidence: 99%